TYPOMORPHISM OF PARAMAGNETIC IMPURITIES IN HALITES FROM THE ZONES OF BASIC-ROCK-EVAPORITE INTERACTION (SIBERIAN PLATFORM) - Istomin V.E.; Mazurov M.P.; Grishina S.N. (My University, 2000)
The EPR method was for the first time used for studying composition, form, and structural transformations of paramagnetic impurities in major generations of halite from the zones of basic-rock-evaporite interaction. The main paramagnetic impurities in natural halites are Mn2+ and Fe3+ and dispersed organic matter. Isomorphous incorporation of Mn2+ into the regular lattice of NaCl is rather limited and was found only in sedimentary halites. The main form of stabilization of Mn2+ in hydrothermal and contact-metasomatic generations of halite are carbonate microphases. Ions Fe3+ concentrate in various forms: clusters, microphases, and independent hydrogoethite and goethite phases. An increase in the degree of contact metamorphism of salts leads to an increase in the dimensionality of Fe3+ accumulations. Ferromagnetic oxides and sulfides are stable in high-temperature contact zones. The dispersed organic matter is also specific in the EPR spectra of halites with a varying degree of metamorphism. The revealed peculiarities of the modes of incorporation of paramagnetic impurities into the real halite structure are a new typomorphic feature suitable for separation and correlation of halite-bearing associations and interpretation of the dynamics of metasomatic mineral formation.